2019
DOI: 10.1371/journal.pone.0220843
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial roles of probiotics on the modulation of gut microbiota and immune response in pigs

Abstract: The importance of probiotics in swine production is widely acknowledged as crucial. However, gaps still remain in the exact roles played by probiotics in modulation of gut microbiota and immune response. This study determined the roles of probiotic Lactobacillus plantarum strain JDFM LP11in gut microbiota modulation and immune response in weaned piglets. L. plantarum JDFM LP11 increased the population of lactic acid bacteria in feces and enhanced the development of villi in the small intestine. Metagenome anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 92 publications
8
109
0
7
Order By: Relevance
“…The high diversity indexes, including Shannon, Simpson, Chao1, and ACE (Abundance-based Coverage Estimator) indicated that Bacillus amyloliquefaciens fsznc-06 or Bacillus pumilus fsznc-09 treatment increased the richness of microbiota in rumen and caecum, compared with the control group. A good digestive tract microbiota benefits the host by regulation of the physiological procedure and mucosal immunity, from producing antimicrobial substances to suppressing the proliferation of digestive tract pathogens [23], leading to a highly efficient rumen function [24] and improving growth performance through improving the digestive tract microbial ecosystem [25]. In the present study, Firmicutes and Bacteroidetes were the two dominant phyla in the rumen and caecum, which is in agreement with previous studies [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…The high diversity indexes, including Shannon, Simpson, Chao1, and ACE (Abundance-based Coverage Estimator) indicated that Bacillus amyloliquefaciens fsznc-06 or Bacillus pumilus fsznc-09 treatment increased the richness of microbiota in rumen and caecum, compared with the control group. A good digestive tract microbiota benefits the host by regulation of the physiological procedure and mucosal immunity, from producing antimicrobial substances to suppressing the proliferation of digestive tract pathogens [23], leading to a highly efficient rumen function [24] and improving growth performance through improving the digestive tract microbial ecosystem [25]. In the present study, Firmicutes and Bacteroidetes were the two dominant phyla in the rumen and caecum, which is in agreement with previous studies [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, L. johnsonii L531 pretreatment also protected animals from S. Infantis-induced intestinal damage (villus loss and ultrastructural damage). This was consistent with a previous report that probiotic supplementation increases the villus height and crypt depth in the intestine of piglets [19].…”
Section: Discussionsupporting
confidence: 94%
“…Associated with clinical and growth outcomes, fecal microbiota was evaluated as a main target for these alternative diets. Many authors have described the great impact of early-life events in mammals, and particularly in pigs, on their future health by shaping immune system development through changes in the pattern of microbial intestinal colonization [44,45]. Several works have demonstrated that aging involves greater richness and alpha diversity in the gut, and in the specific case of pig microbiota, the ecosystem has been described as becoming more homogenous between animals (reduced beta diversity) with age as of weaning [46][47][48].…”
Section: Discussionmentioning
confidence: 99%